Recent studies on age determination of Indian fishes using scales, otoliths and other hard parts - Seshappa, G (Indian Journal of Fisheries, 2011)
At present it is customary to use the growth rings found in the scales, otoliths or other hard parts of fishes to assess the age at different periods of their lives. Though such rings were sometimes discovered in the past in India also, they were rejected in view of the absence of clear summers and winters in our waters as occurring in temperate waters where clear growth differences are known in the fishes and in their above said hard parts. Examination of the scales of Cynoglossus semifasciatus Day at Calicut in the middle of this century proved not only the annual periodicity of the ring formation but also the causes of the same. Such rings or annuli were later found in the other species of Cynoglossus at Calicut and also in many other fishes elsewhere by other workers, though in a few cases there were difficulties because of the occasional occurrence of abnormalities and false checks in the scales, making the interpretations a bit difficult. Later, coverage of more species from different centres revealed the widespread occurrence of growth rings (also called annuli) caused by factors other than seasons alone and their usefulness in age determinations. In the present paper the recent developments made in india in this discipline of fishery biology are briefly reviewed.